1999
DOI: 10.1016/s0378-1097(99)00056-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of enteroaggregative Escherichia coli isolates

Abstract: Forty enteraggregative Escherichia coli (EAggEC) previously characterized by their ability to adhere to HEp-2 cells or/and their hybridization with the 1-kb EAggEC DNA probe were investigated for the presence of adherence factors and heat-stable enterotoxin (EAST1)-encoding genes. Only 45% of the isolates harbored the EAST1-encoding genes as detected by polymerase chain reaction. None of them hybridized with an AAF/II-encoding gene specific DNA probe and 35% (14/40) were positive in a PCR assay using primers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 15 publications
4
27
2
1
Order By: Relevance
“…This finding is in agreement with those of a previous study with a worldwide collection of EAEC isolates (10) and a recent study conducted in Brazil (59). The prevalence of the AAF/II operon is generally reported to be low (13,41,52), and the results of our study are consistent with that finding. Bernier et al (4) have recently reported on the existence of a high level of heterogeneity in the AAF/II operon and demonstrated the use of an aafDA-specific probe for the detection of AAF/II.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in agreement with those of a previous study with a worldwide collection of EAEC isolates (10) and a recent study conducted in Brazil (59). The prevalence of the AAF/II operon is generally reported to be low (13,41,52), and the results of our study are consistent with that finding. Bernier et al (4) have recently reported on the existence of a high level of heterogeneity in the AAF/II operon and demonstrated the use of an aafDA-specific probe for the detection of AAF/II.…”
Section: Discussionsupporting
confidence: 94%
“…The higher frequency of the accessory genes (aggC, aafC, and agg3C) in comparison to the lower frequency of the corresponding structural genes encoding pilin subunit provide evidence for the heterogeneity in the latter. These results are in agreement with those of the earlier studies on the higher prevalence of aggC genes (10,16,41). The presence of agg3C in 22.3% of the EAEC isolates indicated that the agg3 gene or a variant agg3 gene was the second most frequent adhesin after agg.…”
Section: Discussionsupporting
confidence: 93%
“…A similar astA gene frequency has previously been reported among EAEC probe-negative strains (7), but in that study, EAST-1 was detected more frequently in strains from controls than in strains from patients. Okeke et al (19) and Rich et al (22) detected EAST-1 in 23 and 45% of EAEC strains, respectively, but no correlation between the presence …”
Section: Discussionmentioning
confidence: 95%
“…59 The prevalence of EAST-1 among EAEC strains and its contribution to virulence remains unclear. 60,61 Further toxins Figure 1. Enterotoxigenic E. coli (ETEC).…”
Section: Molecular Mechanisms Of Virulencementioning
confidence: 99%